Dutch ships in tropical waters : the development of the Dutch East India Company (VOC) shipping network in Asia 1595-1660 - Parthesius, Robert (Amsterdam studies in the Dutch golden age., 2010)
An engaging and definitive study of the secrets of the vast commercial success of the Dutch East India Company.